2020
DOI: 10.1136/bmjopen-2020-039591
|View full text |Cite
|
Sign up to set email alerts
|

The role of concomitant ligament injury in the development of post-traumatic osteoarthritis after distal radius fractures: a protocol for a systematic review

Abstract: IntroductionTreatment of distal radius fractures (DRFs) aims to restore anatomic position of the fracture fragments and congruity of the articular surface to optimise functional outcomes and prevent osteoarthritis in the long term. While ligament injury of the wrist is often associated with DRFs and sole ligament injuries of the wrist lead to osteoarthritis, it is plausible that concomitant ligament injury in DRFs may aggravate degenerative changes of the wrist. The relationship between concomitant ligament in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…When joint trauma occurs, the articular cartilage degenerates, secondary hyperplasia leads to joint dysfunction, and approximately 12% of patients develop secondary OA [19]. PTOA is mainly manifested as knee pain, swelling, movement disorders, and disability, which seriously affect the patient's quality of life and increases the economic burden on the family [20]. Early conservative treatment or joint replacement may relieve pain and improve function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When joint trauma occurs, the articular cartilage degenerates, secondary hyperplasia leads to joint dysfunction, and approximately 12% of patients develop secondary OA [19]. PTOA is mainly manifested as knee pain, swelling, movement disorders, and disability, which seriously affect the patient's quality of life and increases the economic burden on the family [20]. Early conservative treatment or joint replacement may relieve pain and improve function.…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhizin is a small molecule inhibitor of high mobility group box 1 (HMGB1), which can effectively inhibit inflammation, and has high safety and tolerance [21]. Glycyrrhizin has been clinically used in the treatment of various skin diseases and malignant tumors [7,8,20]. In recent years, glycyrrhizin has also been found to have a protective effect on arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Another long-term follow-up study, focusing on osteoarthritis (OA) of the distal interphalangeal (DIP) joint after a MF fracture, showed that the rate of radiological OA development after a MF fracture was almost equal to the natural degenerative process in the DIP joint in the absence of prior MF fracture and was accompanied by a decrease in range of motion of the DIP joint, which did not clinically affect patient related outcome measures. 23 Therefore, conservative treatment of MF was advocated. The current study showed that only 2% eventually had to undergo surgery.…”
Section: Comparison With Existing Literature and Guidelinesmentioning
confidence: 99%
“…The occurrence of OA is associated with multiple risk factors, such as injury, obesity, genetics, and age. [ 2 , 3 , 4 , 5 ] The pathogenesis of OA is complex. Studies have demonstrated that chondrocyte dysfunction and chronic inflammation are closely related to OA, leading to cartilage destruction.…”
Section: Introductionmentioning
confidence: 99%